STUDY OF LOW RESISTIVITY AND LOW QUALITY RESERVOIR DEVELOPMENT METHOD WITH SENSITIVITY OF WELL STIMULATION AND IMPROVED OIL RECOVERY STARTING TIME IN FIELD X - Irsyad Fahmi Lubis, Muhammad
Low resistivity low quality reservoir is increasingly being considered in the oil and gas industry, from exploration activity to its development. However, in its development, it is often considered uneconomic or not prioritized because of its low recovery factor. Reservoir simulation is carried out on a pattern in field X for 20 years. There are four simulation cases. The first case is natural flow, the second case is water injection, the third case is hydraulic fracturing, and the fourth case is a combination of water injection and hydraulic fracturing. The cases are evaluated based on the value of oil recovery factor. Furthermore, sensitivity analysis is carried out from technical aspect to determine the optimum technical conditions. The economics of these methods will be evaluated using Cost Recovery and Gross Split. Then, the most optimum scenario can be determined based on its oil recovery factor and economy. The result shows that by using water injection at initial and hydraulic fracturing at the end of the first quarter of production time for field X development, an oil recovery factor of 60.84% is obtained, better than other development methods. Further analysis was carried out; it is found that with sensitivity analysis, the optimum technical conditions for the best development method are starting water injection in 2020, starting hydraulic fracturing in 2025, and fracture permeability of 37029 mD. And economically, this scenario results in a better economic output parameter with Gross Split scheme compared to Cost Recovery scheme which results in contractor’s Net Present Value at 10 percent discount rate of (0.42) million USD, government’s Net Present Value at 10 percent discount rate of 8.95 million USD, Internal Rate of Return 8.86%, and Pay Out Time 2.84 years.